Personal Konstruk Siswa Tunarungu Di SMALB Kota Sorong - Evie Syalviana; Jariyah Jariyah; Syahrul Syahrul (LPPM IAIN Sorong, 2022)
The personal construct of each individual is certainly different. There are individuals who easily understand human behavior in their environment. There are also those that take longer. Deaf children tend to be suspicious of their environment. They felt that people around them often mocked them. The existence of this suspicion, makes him often aloof and hostile to the environment. This attitude is also one of the elements inhibiting the development of his personality. This research is a qualitative research with data collection tools using observation, interviews and documentation. Based on the results of the study, it shows that the role of personal personality construct is a theory that emphasizes that every human being has the ability to construct his behavior according to the concept that will be used in implementing every event around their life. The role of teachers, parents and also the environment is very large in the social life of deaf children and affects their social life. Social interaction of deaf children can also be done by means of non-verbal communication (sign language). Public acceptance is very influential on the communication of deaf children